2019
DOI: 10.1126/scitranslmed.aax2863
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial translation overcomes venetoclax resistance in AML through activation of the integrated stress response

Abstract: Venetoclax is a specific B cell lymphoma 2 (BCL-2) inhibitor with promising activity against acute myeloid leukemia (AML), but its clinical efficacy as a single agent or in combination with hypomethylating agents (HMAs), such as azacitidine, is hampered by intrinsic and acquired resistance. Here, we performed a genome-wide CRISPR knockout screen and found that inactivation of genes involved in mitochondrial translation restored sensitivity to venetoclax in resistant AML cells. Pharmacologic inhibition of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(177 citation statements)
references
References 78 publications
5
172
0
Order By: Relevance
“…The respective labelled metabolites were added with or without venetoclax treatment (1 μM, 24 h) to CT26 cells and intracellular metabolites were analysed by LC-MS. Higher label incorporation was found in TCA cycle metabolites using 13 C-glutamine ( Fig. S2A) compared with 13 C-glucose ( Fig. S2B), indicating that glutamine is the main substrate for the TCA cycle in these cells.…”
Section: Venetoclax Inhibits the Tca Cycle Causing Reductive Carboxylmentioning
confidence: 97%
See 2 more Smart Citations
“…The respective labelled metabolites were added with or without venetoclax treatment (1 μM, 24 h) to CT26 cells and intracellular metabolites were analysed by LC-MS. Higher label incorporation was found in TCA cycle metabolites using 13 C-glutamine ( Fig. S2A) compared with 13 C-glucose ( Fig. S2B), indicating that glutamine is the main substrate for the TCA cycle in these cells.…”
Section: Venetoclax Inhibits the Tca Cycle Causing Reductive Carboxylmentioning
confidence: 97%
“…S2B), indicating that glutamine is the main substrate for the TCA cycle in these cells. Consequently, we analysed different metabolites following 13 C-glutamine labelling. This analysis showed that venetoclax treatment increased the levels of glutamate m+5 ( Fig.…”
Section: Venetoclax Inhibits the Tca Cycle Causing Reductive Carboxylmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, running out of ATP in the inner layer of mitochondrion could stimulate the AMPK/PKA pathway, showing a synergistic effect with the amplification of 1q23 [ 39 ]. Using a genome-wide CRISPR knockout screen, Sharon et al [ 49 ] found that gene inactivation involving mitochondrial translation sensitized AML cells with drug resistance to venetoclax. The inhibition of mitochondrial respiration by inhibiting the electron transport chain (ETC) complex 1 is one of the mechanisms by which venetoclax kills AML cells, suggesting that mitochondrial energy metabolism disorders are involved in the resistance of venetoclax.…”
Section: Dysregulation Of Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…The inhibition of mitochondrial respiration by inhibiting the electron transport chain (ETC) complex 1 is one of the mechanisms by which venetoclax kills AML cells, suggesting that mitochondrial energy metabolism disorders are involved in the resistance of venetoclax. The combined use of drugs, such as tedizolid, which target the mitochondrial respiratory chain through different mechanisms, can further enhance the anti-AML effect of venetoclax combined with azacitidine in vivo and in vitro [ 49 , 50 ]. In leukemic stem cells, mutant TP53 perturbed mitochondrial homeostasis by dysregulating transcription factor DP-1 (TFDP1) activation and translocation of phorbol-12-myristate-13-acetate-induced protein 1 (PMAIP1) into the mitochondria, impairing the effector function of BAX/BAK [ 51 ].…”
Section: Dysregulation Of Mitochondrial Energy Metabolismmentioning
confidence: 99%